Comprehensive analysis reveals a 5-gene signature and immune cell infiltration in Alzheimer’s disease with qPCR validation - Jin, Fanmao; Xi, Yuemei; Xie, De; Wang, Qiang (Frontiers in Genetics, 2022)
Over 50 million people around the world currently are suffering from Alzheimer’s disease (AD) without any effective therapy. Neuroinflammation plays a pivotal role in AD, which leads us to probe the profile of immune cell infiltration in AD. Here, we analyzed a microarray dataset (GSE44770) containing 115 AD and 115 control samples to determine biomarkers and immune infiltration characteristics of AD by multiple bioinformatics methods. First, we identified 3,840 DEGs (1892 upregulated and 1948 downregulated) by using the limma package and 2,697 hub genes by constructing a weighted gene correlation network, and they had a total of 2,167 intersecting genes. Second, combining the LASSO logistic regression and SVM-RFE, we obtained five biomarkers (DGKG, MAP3K7IP2, NFKBIE, VIP, and PCCB), which may reveal the key pathogenetic features of AD and serve as diagnostic markers assessed by the ROC curve (AUC = 0.9716) and validation of another AD dataset (GSE33000) (AUC = 0.9388). Third, immune cell infiltration analysis revealed that compared with control samples, plasma cells, CD8 T cells, T follicular helper cells, and activated NK cells infiltrated less in AD; Monocytes, M2 macrophages, and neutrophils infiltrated more in AD. Neutrophils and activated NK cells demonstrated the most significant and negative correlation. Then, Spearman correlation analysis between the five biomarkers and immune infiltrating cells revealed that all of them were significantly associated with plasma cells. Finally, mRNA levels of VIP and PCCB were conformed in a murine AD model. In conclusion, DGKG, MAP3K7IP2, NFKBIE, VIP, and PCCB may be used as diagnostic markers of AD, and the disruption of the delicate immune balance may be a key process in the onset and development of AD.